Tricky Dick and his pals : comical stories, all in the manner of Dr. Heinrich Hoffmann's Der Struwwelpeter - Wortis, Joseph, 1906-1995; Arkin, David; Hoffmann, Heinrich, 1809-1894. (New York : Quadrangle/New York Times Book Co., 1975)
A parody of Heinrich Hoffmann's Der Struwwelpeter, this is a political satire in verse in which Richard Nixon and his associates are shrunk to ill-behaving boys in small-town America, the supposed epicenter of morality.
Weiss, Gerhard. "'Tricky Dick': Struwwelpeter and American Politics." The Lion and the Unicorn, 20.2 (Dec. 1996), p. 217-229.
Keywords: Hoffmann, Heinrich, -- 1809-1894 -- Parodies, imitations, etc; Nixon, Richard M., -- 1913-1994 -- Humor; Conduct of life -- Fiction; Stories in rhyme; United States -- Politics and government -- 1969-1974 -- Humor; Political satire